Evaluation of building period formulas for seismic design. - Kwon, Oh-Sung
Building period formulas in seismic design code are evaluated with over 800 apparent building periods from 191 building stations and 67 earthquake events. The evaluation is carried out with the formulas in ASCE 7-05 for steel and RC moment-resisting frames, shear wall buildings, braced frames, and other structural types. Qualitative comparison of measured periods and periods calculated from the code formulas shows that the formula for steel moment-resisting frames generally predicts well the lower bound of the measured periods for all building heights. But the differences between the periods from code formula and measured periods of low- to-medium rise buildings are relatively high. In addition, the periods of essential buildings designed with the importance factor are about 40% shorter than the periods of non-essential buildings. The code formula for RC moment-resisting frames describes well the lower bound of measured periods. The formula for braced frames accurately predicts the lower bound periods of low-to-medium rise buildings. The formula for shear wall buildings overestimates periods for all building heights. For buildings that are classified as other structural types, the measured building periods can be much shorter than the periods calculated with the code formula. Based on these observations, it is suggested to use Cr factor of 0.015 for shear walls and other structural types.
Keywords: Building period formula; Seismic design; System identification